Diversity of Migratory Waterbirds along the Deli Serdang Coast, North Sumatra - Fachrul Azhari Silalahi; Erni Jumilawaty; Hesti Wahyuningsih (Journal of Sylva Indonesiana, 2026)
Migratory waterbirds rely strongly on wetland ecosystems as staging and refueling sites along their migration routes, including those situated within the East Asian–Australasian Flyway (EAAF) traversing Sumatra. This study aim to record the species diversity, evenness, and community similarity of migratory waterbirds along the Deli Serdang coast, North Sumatra. Field surveys were conducted from September to October 2025 at three intertidal mudflat sites: Paluh Getah, Muara Sei Tuan, and Bagan Serdang. Species identification was performed using binoculars, a monocular telescope, and photographic documentation. Waterbird assemblages were quantified using the concentration count and block methods, followed by calculation of the Shannon–Wiener diversity index (H′), species evenness (E), and inter-site similarity (IS). A total of 21 migratory waterbird species were recorded, with the Pacific Golden Plover (Pluvialis fulva) representing the most abundant species (582 individuals). Diversity (H') indices across all sites indicated moderate diversity, whereas E values were consistently high, reflecting relatively uniform species distributions. The most similar avian community was observed between Paluh Getah and Muara Sei Tuan (93.75%), likely attributable to similar habitat structure and levels of anthropogenic disturbance. These findings demonstrated that the mudflats of Deli Serdang constitute an ecologically important staging habitat for migratory waterbirds along the EAAF, including several species of conservation concern. Strengthened habitat protection and management are therefore essential to support the existence of migratory populations dependent on this coastal region.